ANALISIS LAYANAN KENAIKAN JABATAN FUNGSIONAL DOSEN UIN AR-RANIRY BANDA ACEH - AR, Khairan; Tassia, Fransisca; Nst, Raihana Ramadhanulita; Widya, Icha; Ardiansyah, Khairun (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2023)
The purpose and objective of this study is to analyze the effect of functional promotion services on the satisfaction of lecturers at UIN Ar-Raniry Banda Aceh. Exogenous attributes are based on service theory, which consists of the following attributes: reliability, assurance, tangible, empathy, and responsiveness. After testing the path analysis, the results showed that the total influence of the reliability, assurance, and tangibility attributes on lecturer satisfaction obtained a value of 0.742. These results indicate that the attributes of reliability, assurance, and tangibility have a strong and significant effect on the attributes of lecturer satisfaction. Meanwhile, the results obtained showed that the reliability, assurance, and tangibility attributes on the empathy attribute obtained a total influence value of 0.703. That is, the three attributes have a strong and significant effect on lecturer satisfaction. In addition, the results obtained show that the reliability, assurance, and tangibility attributes have a total effect of 0.634 responsiveness attributes. These results indicate that the reliability, assurance, and tangibility attributes have a strong and significant effect on the responsiveness attribute. Measurement of empathy and responsiveness attributes to satisfaction in total obtained a value of 0.723. These results mean that the attributes of empathy and responsiveness have a strong and significant effect on the attributes of lecturer satisfaction in the process of managing their functional positions.